CALCULATION OF ELECTROMOTIVE FORCE AT INDUCTION SEISMIC RECEIVER OUTPUT FROM ITS EXPOSURE TO SEISMIC RELAY WAVE - A. E. Vinogradov; N. G. Kukhalski (Наука и техника)
An induction seismic receiver is widely applied in many guarding devices (1К18 «Realiya», PS-75 «Gerb» and others) which are used for detection of moving surface objects.  The receiver makes it possible to register soil vibrations caused by the object action. An inertial element of such seismic receiver is a cylindrical coil connected with the body by means of two flat springs.The paper proposes a method for calculation of electromotive force (EMF) at induction seismic receiver output when it is exposed to seismic Relay wave on the basis of a differential equation for motion of the inertial element with due account of transient processes of forced vibrations and damping. The seismic receiver damping is a coil form where k of the spool, in which surface Foucault currents are induced.Results of modeling and experimental investigations have shown that the proposed methodology for EMF calculation, which is induced in the seismic receiver, allows faithfully to model signals at induction seismic receiver output that can be rather useful for mathematical modeling of surface object motion seismograms.